Vestige of Stone: Pavilion Stångehuvud - Malm, Olivia (My University, 2021)
Stångehuvud is a nature reserve in Lysekil where not only its nature, proximity to the sea and spectacular granite landscape is of importance. A predominant part of its identity is also related to human activity and intervention - the traces of sharp scars left in the granite from the stone industry as well as the spirit and persistence of a person who singlehandedly came to save the landscape for the generations to come. They all play a part in creating the collected identity of Stångehuvud, all part of how we perceive and value the site today. Growing up in the small coastal town of Lysekil, I can see how my own identity in many was has been shaped by the surrounding landscapes. The strong salty winds, the coarse red granite and the open horizon of Stångehuvud becoming a multifaceted identity-bearer for many. The idea behind this thesis grew from a personal fascination of the landscape and history of the site. From the anecdotes of the stonemasons of my own family, spending their days in the quarries of Stångehuvud, as well the alluring stories of the brave and persistent Calla Curman refusing to observe the fragmentations of the natural granite landscape. These historical and contemporary values created an interest in how architecture can be positioned in the perception and experience of a landscape. Containing and highlighting historical details, artefacts and stories while also becoming a contemporary meeting place where history, culture and landscape can intersect. Through research by design, this thesis aims towards creating an understanding of the possibilities of the relationship between architecture and landscape by exploring the visible and invisible representations of architecture and tectonics. The goal is to highlight the sometimes conflicting history of Stångehuvud - to raise awareness of the human interactions that came to shape, shatter and save the nature reserve. Through the addition of a museum pavilion and community space I aim to create a new platform for these stories to be shared, creating additional values to the experience of the nature reserve today.
Keywords: Stångehuvud, museum, local history, landscape